ANALISIS PENGARUH INFORMASI STOCK SPLIT TERHADAP ABNORMAL RETURN SAHAM DAN VOLUME PERDAGANGAN SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI BEI (Periode Tahun 2009 â€“ 2013) - B51111015, Yati Agustianingsih (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
The aim of this study is to analyze the determine the effect of the stock split information Abnormal Return and Trading Volume Activity that occurs in companies listed in Indonesia Stock Exchange (IDX). Sampled companies are companies listed on the Stock Exchange the stock split during the period 2009-2013. By using purposive sampling and obtaining results of 15 companies that meet the criteria for the research sample. In this study using event study method and approach of market adjusted model. While testing the hypothesis tested using parametric statistical tests Paired Sample T-test. The results of the study showed that there was no significant effect of the average abnormal return before and after the stock split on the first alternative hypothesis.Â  While in the second alternative hypothesis also obtained results that there is no significant effect on average trading volume before and after the stock split announcement. Keyword : Stock Split, Abnormal Return, Tranding Volume Activity